2013
DOI: 10.1111/ijfs.12287
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of two extraction procedures for determination of bioactive compounds in some berries used for daily food consumption

Abstract: Summary Two extractions with methanol and water were used to determine the antioxidant and binding properties of some berries as a supplement to food. Fluorometry, FTIR spectra and radical scavenging assays were used for characterisation of bioactive compounds (polyphenols, flavonoids, flavanols and tannins) and the levels of their antioxidant activities (AAs). The contents of bioactive compounds and AAs in water and methanol polyphenol extracts in gooseberries, blueberries and cranberries differed, but not al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 37 publications
(70 reference statements)
1
14
1
Order By: Relevance
“…Polyphenols (mg GAE g À 1 DW) in water extracts of gooseberries and blueberries were 6.2470.6 and 57.4774.2 and the TAC (mM TE g À 1 DW) determined by ABTS and CUPRAC assays were for gooseberries and blueberries, respectively [12]. The results shown in Table 2 slightly differ from the results reported previously [2,12], depending on the solvent used, its ratio to the dry material and also on the time and type of extraction. The optimization of ultrasound operational parameters (solvent polarity, sample particle size), according to a specific plant matrix (leaves, flowers, stems) is also of main importance in order to achieve high extraction efficiency [23].…”
Section: Bioactive Compoundscontrasting
confidence: 54%
See 2 more Smart Citations
“…Polyphenols (mg GAE g À 1 DW) in water extracts of gooseberries and blueberries were 6.2470.6 and 57.4774.2 and the TAC (mM TE g À 1 DW) determined by ABTS and CUPRAC assays were for gooseberries and blueberries, respectively [12]. The results shown in Table 2 slightly differ from the results reported previously [2,12], depending on the solvent used, its ratio to the dry material and also on the time and type of extraction. The optimization of ultrasound operational parameters (solvent polarity, sample particle size), according to a specific plant matrix (leaves, flowers, stems) is also of main importance in order to achieve high extraction efficiency [23].…”
Section: Bioactive Compoundscontrasting
confidence: 54%
“…The efficacy of the individual antioxidants and the efficacy of a combination of two antioxidants were measured using fluorescence spectroscopy and showed a synergistic effect. Our very recent results [1,2,12,13] showed that the fluorescence is significantly quenched, because of the conformation of proteins, phenolic acids and flavonoids. Our result is in agreement with others that quercetin, as an aglycon, is more hydrophobic and demonstrates strong affinity toward HSA.…”
Section: Emission Spectral Studiesmentioning
confidence: 95%
See 1 more Smart Citation
“…Important factors in the process are solvent type, extraction time and temperature [9]. Solvents or co solvents with different polarities such as ethanol and water [5,10,11] and/or organic solvents [4,6,7] can be employed for solid-liquid extractions in heat-reflux systems. Furthermore, non-conventional methods (ultrasound, pulsed electric field, enzyme digestion, extrusion, microwave heating, ohmic heating, supercritical fluids) are more environment friendly due to decreased use of synthetic and organic chemicals and reduced operational time, enhancing extract yield and quality [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, from samples after heat treatment , we could only quantify catechin and epicatechin. Previous research identified quercetin, rutin, myricetin, epicatechin, catechin and kaempferol in cape gooseberry [121,122,[116][117][118]124] and although we replicated the procedures of extraction, hydrolysis (if required) and analysis, we could not come up with the same results. We therefore limit the discussion to catechin and epicatechin; the fate of these compounds is presented in figure 4.5.…”
Section: Flavonoidsmentioning
confidence: 71%